Analisis Tindak Tutur Ilokusi dalam Video Pembelajaran Kelas 12 SMA/SMK dalam Kanal YouTube Suparti Timbul - Moh. Ilman Akbar Al Izaaki; Hanifah Ainurohmah; Ainna Galuh Pratiwi; Anggita Rahma Aprilianti; Deane Rahmah Indriawati; Asep Purwo Yudi Utomo; Iwan Hardi Saputro; Ramadhan Kusuma Yuda (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the illocutionary speech acts used by the teacher in the Indonesian language learning videos on the YouTube channel